“Standing on common ground” - a qualitative study of self-management support for patients with multimorbidity in primary health care - Freilich, Joel (BMC Fam Pract, 2020)
BACKGROUND: Multimorbidity, the co-existence of two or more chronic conditions in an individual, is present in most patients over 65 years. Primary health care (PHC) is uniquely positioned to provide the holistic and continual care recommended for this group of patients, including support for self-management. The aim of this study was to explore professionals’, patients’, and family caregivers’ perspectives on how PHC professionals should support self-management in patients with multimorbidity. This study also includes experiences of using telemedicine to support self-management. METHODS: A mixed qualitative method was used to explore regular self-management support and telemedicine as a tool to support self-management. A total of 42 participants (20 physicians, 3 registered nurses, 12 patients, and 7 family caregivers) were interviewed using focus group interviews (PHC professionals), pair interviews (patients and family caregivers), and individual interviews (registered nurses, patients, and family caregivers). The study was performed in urban areas in central Sweden and rural areas in southern Sweden between April 2018 and October 2019. Data were analyzed using content analysis. RESULTS: The main theme that emerged was “Standing on common ground enables individualized support.” To achieve such support, professionals needed to understand their own views on who bears the primary responsibility for patients’ self-management, as well as patients’ self-management abilities, needs, and perspectives. Personal continuity and trustful relationships facilitated this understanding. The findings also indicated that professionals should be accessible for patients with multimorbidity, function as knowledge translators (help patients understand their symptoms and how the symptoms correlated with diseases), and coordinate between levels of care. Telemedicine supported continual monitoring and facilitated patient access to PHC professionals. CONCLUSION: Through personal continuity and patient-centered consultations, professionals could collaborate with patients to individualize self-management support. For some patients, this means that PHC professionals are in control and monitor symptoms. For others, PHC professionals play a less controlling role, empowering patients’ self-management. Development and improvement of eHealth tools for patients with multimorbidity should focus on improving the ability to set mutual goals, strengthening patients’ inner motivation, and including multiple caregivers to enhance information-sharing and care coordination. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12875-020-01290-y.